How effective are IAEA Safeguards? The case of Iran 2003-2006 - Young-Stewart, Justin Stephane (Université d'Ottawa | University of Ottawa, 2018)
The purpose of this paper is to critically examine the International Atomic Energy Agency (IAEA) safeguards system, a set of technical measures through which the Agency aims to prevent the diversion of nuclear energy from peaceful purposes to military uses. The main finding of this paper is that the Agency’s safeguards system faces challenges in the initial detection and reporting of non-compliance. To assess the effectiveness of the IAEA safeguards, this paper looks at the case of Iran (2003-2006) on two levels: (a) capability of the Agency to detect undeclared nuclear material, nuclear activities, and nuclear facilities; and (b) capacity of safeguards as an early warning system to the international community. Following a section on the link between nuclear energy and nuclear weapons, the evolution of the safeguards regime is examined in order to fully understand the nature and scope of the Agency’s activities in Iran. This paper demonstrates that, despite improvements over decades, the safeguards regime is not perfect, particularly as it relates to the detection of undeclared nuclear material, activities, and facilities. However, where the Agency is considerably more effective is in its capacity as an early warning system to the international community. The last part of the paper offers the major conclusions on the capabilities and limitations of the safeguards system, including the implications on the IAEA’s ability to monitory and verify Iran’s commitments under the Joint Comprehensive Plan of Action.